From employees to entrepreneurs: Does migration matter in blue-collar workers’ transition? - Natalia, Christiayu; Pratomo, Devanto Shasta; Syafitri, Wildan (Publisher of Widyagama University of Malang (UWG Press), 2024)
Transitioning into entrepreneurship can offer a viable path for former blue-collar workers to reenter the workforce following widespread job losses during the COVID-19 pandemic. This study investigates the critical roles of adaptability and resilience in facilitating this transition, with particular attention to how migration status influences success in becoming either formal or informal entrepreneurs. Utilizing detailed microdata from the August 2021 Labor Force Survey (Survei Angkatan Kerja Nasional - SAKERNAS), the study applies a multinomial logistic regression model to examine the transition patterns of these former workers. The findings indicate that former migrant blue-collar workers are more inclined to shift towards formal entrepreneurship rather than informal ventures. This suggests the importance of implementing supportive policies aimed at fostering entrepreneurial initiatives among blue-collar workers. Such policies could mitigate the risks associated with job losses, particularly in times of crisis, and provide a safety net by encouraging entrepreneurship. By facilitating entrepreneurial activity, these policies would not only bolster economic resilience but also offer alternative routes for workforce recovery, ultimately contributing to job security, financial stability, and long-term economic sustainability in the face of ongoing uncertainties.JEL ClassificationÂ C25; J24; J63